2020
DOI: 10.1007/s11606-020-06242-x
|View full text |Cite
|
Sign up to set email alerts
|

See One, Do One, Forget One: Early Skill Decay After Paracentesis Training

Abstract: INTRODUCTION:Internal medicine residents perform paracentesis, but programs lack standard methods for assessing competence or maintenance of competence and instead rely on number of procedures completed. This study describes differences in resident competence in paracentesis over time. METHODS: From 2016 to 2017, internal medicine residents (n = 118) underwent paracentesis simulation training. Competence was assessed using the Paracentesis Competency Assessment Tool (PCAT), which combines a checklist, global s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Most recently, a study of internal medicine residents trained in paracentesis skills showed that skill decay was mitigated if booster training occurred at 3 months rather than 6 months. 42 These two investigations Open access shed light on the impact of booster training on procedural skills in nonsurgeons but are imperfect as proxies for hospitalists, who are no longer trainees and have accumulated more experience. Insights from studies on monitoring hospitalist performance in non-procedural skills are also germane in concept, as they focus on collecting and reporting objective individual-level 16 and group-level metrics, 13 approaches applicable to procedural competence tracking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, a study of internal medicine residents trained in paracentesis skills showed that skill decay was mitigated if booster training occurred at 3 months rather than 6 months. 42 These two investigations Open access shed light on the impact of booster training on procedural skills in nonsurgeons but are imperfect as proxies for hospitalists, who are no longer trainees and have accumulated more experience. Insights from studies on monitoring hospitalist performance in non-procedural skills are also germane in concept, as they focus on collecting and reporting objective individual-level 16 and group-level metrics, 13 approaches applicable to procedural competence tracking.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two of 38 eligible hospitalists participated. The average age was 36.5 (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) years. Participants reported an average of 5.9 (range 1-14) years in practice.…”
Section: Baseline Performancementioning
confidence: 99%
“…Regardless of how rarely these cases present in the clinical setting, we know that (1) faculty must be prepared to handle them, especially for those practicing in community affiliated centers, and (2) if they do not continually practice these skills, they become vulnerable to procedural decay. 11,12 Strategies exist to help trainees achieve, maintain, and assess their procedural competency. These include procedure training sessions, just-in-time teaching sessions, and competency-based skills assessments before allowing performance in the clinical arena.…”
Section: Discussionmentioning
confidence: 99%
“…Faculty may go months to years between performing these procedures, as opportunities are infrequent and trainees often make the first attempt. Regardless of how rarely these cases present in the clinical setting, we know that (1) faculty must be prepared to handle them, especially for those practicing in community affiliated centers, and (2) if they do not continually practice these skills, they become vulnerable to procedural decay 11,12 . Strategies exist to help trainees achieve, maintain, and assess their procedural competency.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Internal medicine (IM) program directors and residents commonly rely on counting a small number of procedures as a proxy for competence, as no reliable method exists for determining competence in procedural training. 6,7…”
mentioning
confidence: 99%